2017
DOI: 10.1007/s40121-017-0168-8
|View full text |Cite|
|
Sign up to set email alerts
|

Expanding Antimicrobial Stewardship to Urgent Care Centers Through a Pharmacist-Led Culture Follow-up Program

Abstract: IntroductionUrgent care centers represent a high-volume outpatient setting where antibiotics are prescribed frequently but resources for antimicrobial stewardship may be scarce. In 2015, our pharmacist-led Emergency Department (ED) culture follow-up program was expanded to include two urgent care (UC) sites within the same health system. The UC program is conducted by ED and infectious diseases clinical pharmacists as well as PGY1 pharmacy residents using a collaborative practice agreement (CPA). The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Similarly, observing the benefits of AMS involvement on improved outcomes such as appropriate microbiological specimens being taken and receipt of directed therapy are also not surprising. Other studies with pharmacist-led initiatives have shown similar results and improved overall appropriateness of antimicrobial therapy [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, observing the benefits of AMS involvement on improved outcomes such as appropriate microbiological specimens being taken and receipt of directed therapy are also not surprising. Other studies with pharmacist-led initiatives have shown similar results and improved overall appropriateness of antimicrobial therapy [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 71%
“…These stewardship interventions did not utilize a pharmacist. More recent literature evaluated the impact of a pharmacist‐led culture follow‐up program in the UC setting 17‐19 . Dumkow and colleagues demonstrated the impact of a pharmacist on decreasing antibiotic use through a collaborative practice agreement in asymptomatic patients with positive GAS cultures originally seen in the emergency department/UC.…”
Section: Discussionmentioning
confidence: 99%
“…A descriptive pilot study conducted at our site of all 2016 data demonstrated that during the 1-year period 1,461 positive urgent care culture results were reviewed by clinical pharmacists for antimicrobial appropriateness. 17 Of these, 320 (22%) required pharmacist intervention in the form of a follow-up telephone call. Furthermore, 106 (33%) required a new antibiotic prescription at follow-up.…”
Section: Methodsmentioning
confidence: 99%